Progress in the influence of recycled construction and demolition mineral-based blends on the physical–mechanical behaviour of ternary cementitious matrices. (15th August 2022) - Monasterio, Manuel; Caneda-Martínez, Laura; Vegas, Iñigo; Frías, Moisés
Highlights: Combining the fine fraction of CDW (glass and concrete) yields viable pozzolans. Their use at 7% replacement level gives cements compliant with current standards. Blended mortars show slightly lower mechanical strength and resistivity values. Calcareous concrete wastes increase capillary absorption more than siliceous ones. Abstract: The serious technical and environmental problems associated with the management of construction and demolition wastes (CDW) have led to a worldwide growing interest in the recycling of that waste stream as secondary raw material for sustainable building applications. This research work investigates the physical and mechanical behaviour of mortars made with ternary cements containing 7% of a binary recycled CDW mixture comprising the fine fraction (<5 mm) of recycled concrete waste (both siliceous and calcareous nature) in combination with recycled laminar glass in three different proportions (1/1, 1/2, and 2/1, respectively). To this end, the chemical composition and fineness of the anhydrous ternary cements were analysed, as well as their behaviour in paste and mortar matrices, in both fresh and hardened states, verifying the requirements established by the applicable standards. The results attest to the viability of using these ternary cements, as their performance is comparable to that of an ordinary Portland cement (OPC), without evidencing any significant dependence on the glass content. The compressive strength values decrease by 7–8% with respect to that of the OPC mortar, revealing the prevalence of the filler effect over the pozzolanic reaction. The ternary cements analysed in this study met the chemical, physical and mechanical requirements for the elaboration of future eco-efficient cements.